The MoveOn effect : the unexpected transformation of American political advocacy - Karpf, David, 1978- (New York ; Oxford : Oxford University Press, 2012)
The Internet is facilitating a generational transition among American political advocacy organizations. This book provides a detailed exploration of how 'netroots' advocacy groups - MoveOn.org, DailyKos.com, DemocracyforAmerica.com, and the Progressive Change Campaign Committee - differ from 'legacy' peer organizations.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Political participation -- Technological innovations -- United States; Internet in political campaigns -- United States; Blogs -- Political aspects -- United States; Internet -- Political aspects -- United States